Survival Analysis of Ichimoku Cloud Indicator Benchmarked on the S&P 500 Index - Lutey, Matt; Rayome, Dave (Journal of Applied Business and Economics, 2022)
This paper implements a genetic algorithm of 20 input variables (technical indicators) outlined by the Bank of St. Louis Fed’s research department updated to include newly adopted technical indicators Ichimoku cloud. The research is tested over the 1980-2016 period and benchmarked on the S&P 500 Large Cap Index. The hypothesis is to see if investors may gain additional information from using technical indicators in their asset allocation strategy. The results show through stepwise regression that moving averages, and Ichimoku cloud indicators may convey information to investors although there may be additional macroeconomic information not picked up by the technical signals that should be included in the system of equations. The results show from 1980-2016 the genetic algorithm strategy produces total return of 3308.31 percent versus the S&P 500 1909.90 percent. The result is .16608 with p-value of 0.000 for the Moving Average 3,12 and 0.24 for Ichimoku Cloud Indicator based on the 1,26 period. For Ichimoku Indicator 26,52 it is 0.000 and for 1,52 0.009.